Coarse-grain hard alloy as well as preparation method and application thereof

By using a combination of tungsten carbide, binder and additives in crude crystal carbide, combining the tightly interlaced structure of ultra-coarse crystal tungsten carbide and crude crystal tungsten carbide and the solid solution effect of tantalum carbide and niobium carbide, the high temperature of the alloy is solved The problem of insufficient wear resistance and toughness has significantly improved its service life and performance under harsh working conditions.

CN119243007APending Publication Date: 2025-01-03ZHUZHOU HARD ALLOY GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411201981.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing coarse crystal carbides have insufficient wear resistance at high temperatures, poor toughness and thermal fatigue resistance, resulting in abnormal failure phenomena such as excessive wear and fragmentation under harsh working conditions, affecting operating efficiency.

Method used

Using the combination of tungsten carbide, binder and additives (such as tantalum carbide and niobium carbide), the high temperature of the alloy is enhanced by the tight interlacing of ultra-coarse crystal tungsten carbide and crude crystal tungsten carbide. Wear resistance and strength reduce the defect rate of "cobalt pool" and extend service life.

Benefits of technology

It significantly improves the high-temperature wear resistance and strength of the alloy, extends the service life, and reduces the risk of abnormal failure. It is suitable for road surface milling, pile foundation spin digging, coal mining and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243007A_ABST
    Figure CN119243007A_ABST
Patent Text Reader

Abstract

The coarse grain hard alloy is prepared from tungsten carbide, a binding agent, an additive and a forming agent. The additive is tantalum carbide and / or niobium carbide, based on the total weight of the tungsten carbide, the binder and the additive, the use amount of the tungsten carbide is 89.5 wt%-95.99 wt%, and the use amount of the additive is 0.01 wt%-0.5 wt%; wherein the tungsten carbide comprises ultra-coarse grain tungsten carbide and coarse grain tungsten carbide, and based on the total weight of the tungsten carbide, the content of the ultra-coarse grain tungsten carbide is 40wt%-60wt%, and the balance is the coarse grain tungsten carbide; the Fisher particle size of the ultra-coarse-grain tungsten carbide is 18 [mu] m-25 [mu] m, and the Fisher particle size of the coarse-grain tungsten carbide is 6 [mu] m-9 [mu] m. The coarse grain hard alloy prepared through the method is good in wear resistance and long in service life, and can be applied to the fields of pavement milling, pile foundation rotary excavating, coal mining and the like. The invention further relates to a preparation method and application of the coarse grain hard alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cemented carbide, and in particular relates to a coarse-grained cemented carbide and a preparation method and application thereof. Background Art

[0002] In the fields of road milling, pile foundation rotary drilling, coal mining, tunnel excavation, etc., cemented carbide is the key part for directly crushing various types of rocks. During service, cemented carbide is often subjected to very high shear stress and impact force. When this shear stress and impact force exceed the bearing limit of cemented carbide, cemented carbide will break. Therefore, this type of cemented carbide is required to have excellent shear resistance, impact toughness and high fracture toughness. At the same time, due to the continuous friction and wear between rock and cemented carbide, this type of alloy is also required to have high wear resistance.

[0003] However, improving the wear resistance of the alloy is likely to reduce the toughness of the alloy, and enhancing the toughness of the alloy is likely to weaken its wear resistance. Conventional coarse-grained cemented carbide is difficult to achieve a balance between the above-mentioned properties, especially under dense full-rock complex service conditions, due to insufficient high-temperature wear resistance, poor toughness and thermal fatigue resistance, etc., the alloy is prone to abnormal failures such as excessive wear, broken teeth and cracking, which seriously affects the operating efficiency. Summary of the invention

[0004] Based on the above, the main purpose of the present invention is to provide a coarse-grained cemented carbide and its preparation method and application. The coarse-grained cemented carbide provided by the present invention has good strength and fracture toughness, so it can improve the wear resistance of the alloy and greatly increase the service life of the coarse-grained cemented carbide under harsh working conditions. It can be used in road milling, pile foundation rotary drilling, coal mining, tunnel excavation and other fields.

[0005] To this end, in a first aspect, the present invention provides a coarse-grained cemented carbide, wherein the raw materials for preparing the coarse-grained cemented carbide include tungsten carbide, a binder, an additive and a forming agent; the additive is tantalum carbide and / or niobium carbide, and based on the total weight of tungsten carbide, the binder and the additive, the amount of tungsten carbide is 89.5wt% to 95.99wt%, the amount of the additive is 0.01wt% to 0.5wt%, and the balance is the binder;

[0006] The tungsten carbide comprises ultra-coarse-grained tungsten carbide and coarse-grained tungsten carbide. Based on the total weight of tungsten carbide, the content of the ultra-coarse-grained tungsten carbide is 40wt% to 60wt%, and the remainder is coarse-grained tungsten carbide; the Fisher grain size of the ultra-coarse-grained tungsten carbide is 18μm to 25μm, and the Fisher grain size of the coarse-grained tungsten carbide is 6μm to 9μm.

[0007] Specifically, in the coarse-grained cemented carbide of the present invention, the raw material tungsten carbide includes ultra-coarse-grained tungsten carbide and coarse-grained tungsten carbide. On the one hand, the ultra-coarse-grained tungsten carbide and the coarse-grained tungsten carbide ensure that the alloy has high fracture toughness. On the other hand, the tungsten carbide grains of different sizes are closely staggered, so that the thickness of the cobalt phase filled between the tungsten carbides is reduced and the distribution is more uniform, which greatly reduces the probability of defects such as "cobalt pools" in the alloy. At the same time, additives are added to cooperate with the binder to strengthen the binder phase without reducing the toughness of the alloy, thereby increasing the hardness of the alloy, greatly improving the high-temperature wear resistance and strength of the alloy, and thus extending the service life of the alloy.

[0008] As a specific embodiment of the present invention, preferably, the binder is cobalt powder. According to the present invention, the additives tantalum carbide and niobium carbide can be dissolved in the binder phase Co, so that the Co phase is strengthened without reducing the toughness of the alloy, the hardness of the alloy is increased, and the high-temperature wear resistance and strength of the alloy are greatly improved, thereby extending the service life of the alloy.

[0009] As a specific embodiment of the present invention, preferably, based on the total weight of tungsten carbide, cobalt powder and additives, the amount of cobalt powder is 4wt% to 10wt%.

[0010] As a specific embodiment of the present invention, preferably, the cobalt powder has a Fisher particle size of 0.6 μm to 2.0 μm.

[0011] As a specific embodiment of the present invention, preferably, the composite tungsten carbide is composed of ultra-coarse-grained tungsten carbide and coarse-grained tungsten carbide. Based on the total weight of the composite tungsten carbide, the content of the ultra-coarse-grained tungsten carbide is 40wt% to 60wt%, and the remainder is coarse-grained tungsten carbide.

[0012] As a specific embodiment of the present invention, preferably, the additive has a Fisher particle size of 0.8 μm to 2.5 μm.

[0013] As a specific embodiment of the present invention, preferably, the ultra-coarse-grained tungsten carbide powder is not doped with a thickening agent, and preferably the thickening agent includes an alkali metal. According to the present invention, ultra-coarse-grained tungsten carbide powder not doped with a thickening agent such as an alkali metal is used as a raw material, and the ultra-coarse-grained tungsten carbide has a low content of metal impurities, which can reduce the number of alloy micropores.

[0014] As a specific embodiment of the present invention, preferably, the molding agent is polyethylene glycol and / or paraffin. Preferably, the amount of the molding agent is 2.0wt% to 3.0wt% based on the total weight of tungsten carbide, cobalt powder and additives.

[0015] As a specific embodiment of the present invention, preferably, when the molding agent is polyethylene glycol and paraffin, the weight ratio of the two is (1-3):1.

[0016] As a specific embodiment of the present invention, preferably, the molecular weight of the polyethylene glycol is 1500Da to 6000Da, such as 1500Da, 1600Da, 1800Da, 2000Da, 2200Da, 2400Da, 2600Da, 2800Da, 3000Da, 3200Da, 3400Da, 3600Da, 3800Da, 4000Da, 4200Da, 4400Da, 4600Da, 4800Da, 5000Da, and any value therebetween.

[0017] As a specific embodiment of the present invention, preferably, the molecular weight of the polyethylene glycol is 3000Da to 5000Da.

[0018] As a specific embodiment of the present invention, preferably, the molecular weight of the polyethylene glycol is 3500Da to 4500Da.

[0019] As a specific embodiment of the present invention, preferably, the molding agent is polyethylene glycol PEG 4000 and / or 52# paraffin.

[0020] As a specific embodiment of the present invention, preferably, the average grain size of the coarse-grained cemented carbide is 2.4 μm to 6.0 μm, such as 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5.0 μm, 5.2 μm, 5.4 μm, 5.6 μm, 5.8 μm, 6.0 μm, and any value therebetween.

[0021] In the present invention, the average grain size refers to the average grain size of the The grain size is measured by the metal average grain size determination method.

[0022] As a specific embodiment of the present invention, preferably, the density of the coarse-grained cemented carbide is 14.20 g / cm 3 ~15.30g / cm 3 .

[0023] To this end, in a second aspect, the present invention provides a method for preparing the above-mentioned coarse-grained cemented carbide, comprising the following steps:

[0024] S1: mixing and grinding coarse-grained tungsten carbide, a binder, an additive and a forming agent to obtain a first mixed slurry;

[0025] S2: mixing and grinding the ultra-coarse-grained tungsten carbide and the first mixed slurry obtained in step S1 to obtain a second mixed slurry;

[0026] S3: drying, granulating, and pressing the second mixed slurry obtained in step S2 to obtain a green body;

[0027] S4: Sintering the green body obtained in step S3 to obtain the coarse-grained cemented carbide.

[0028] As a specific embodiment of the present invention, preferably, in step S1, the mixed grinding includes a first wet grinding.

[0029] As a specific embodiment of the present invention, preferably, the conditions of the first wet grinding include: a ball-to-material ratio of (1.5-3.5):1, a rotation speed of 20-60 rpm, and a ball milling time of 10h-30h. Specifically, the ball-to-material ratio here refers to the ratio of the weight of the grinding body to the total weight of the coarse-grained tungsten carbide, the binder and the additive.

[0030] As a specific embodiment of the present invention, preferably, wet grinding media is used in the first wet grinding process.

[0031] As a specific embodiment of the present invention, preferably, the wet grinding medium comprises alcohol with a volume concentration of 90-95%. Preferably, based on the total amount of ultra-coarse-grained tungsten carbide, coarse-grained tungsten carbide, binder and additives, the amount of alcohol added satisfies a solid-liquid ratio of 0.12L / kg to 0.35L / kg.

[0032] As a specific embodiment of the present invention, preferably, in step S2, the mixed grinding includes a second wet grinding.

[0033] As a specific embodiment of the present invention, preferably, the conditions of the second wet grinding include: a ball-to-material ratio of (1.1-2.0):1, a rotation speed of 20-60 rpm, and a ball milling time of 10 h to 35 h. Specifically, the ball-to-material ratio here refers to the ratio of the weight of the grinding body to the total weight of the ultra-coarse-grained tungsten carbide, coarse-grained tungsten carbide, binder and additives.

[0034] As a specific embodiment of the present invention, preferably, in step S3, the drying conditions include: a drying temperature of 80° C. to 120° C., and a drying time of 2 h to 4 h.

[0035] As a specific embodiment of the present invention, preferably, in step S4, the firing conditions include: a firing temperature of 1410° C. to 1550° C., and a firing time of 1 h to 3 h.

[0036] As a specific embodiment of the present invention, preferably, the firing includes pressure sintering, preferably pressure sintering in an inert gas.

[0037] As a specific embodiment of the present invention, preferably, the inert gas includes at least one of nitrogen, argon and helium.

[0038] As a specific embodiment of the present invention, preferably, the inert gas partial pressure is 1 MPa to 10 MPa.

[0039] As a specific embodiment of the present invention, preferably, the pressure sintering is performed in argon gas, and more preferably, the partial pressure of argon gas is 1 MPa to 10 MPa.

[0040] To this end, in a third aspect, the present invention provides an application of the above-mentioned coarse-grained cemented carbide or the coarse-grained cemented carbide prepared by the above-mentioned preparation method in road milling, pile foundation rotary drilling, coal mining, and tunnel excavation.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. The coarse-grained cemented carbide of the present invention adopts ultra-coarse-grained tungsten carbide and coarse-grained tungsten carbide as raw materials. On the one hand, the ultra-coarse-grained tungsten carbide and coarse-grained tungsten carbide ensure that the alloy has high fracture toughness. On the other hand, the tungsten carbide grains of different sizes are closely staggered, so that the thickness of the cobalt phase filled between the tungsten carbides is reduced and the distribution is more uniform, which greatly reduces the probability of defects such as "cobalt pool" in the alloy.

[0043] 2. The coarse-grained cemented carbide of the present invention adds a small amount of tantalum carbide and / or niobium carbide to be dissolved in the binder phase Co, so that the Co phase is strengthened without reducing the toughness of the alloy, the hardness of the alloy is increased, and the high-temperature wear resistance and strength of the alloy are greatly improved, thereby extending the service life of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a metallographic photograph of the coarse-grained cemented carbide prepared in Example 1.

[0045] Figure 2 This is a metallographic photograph of the coarse-grained cemented carbide prepared in Example 2.

[0046] Figure 3 This is a metallographic photograph of the coarse-grained cemented carbide prepared in Example 3.

[0047] Figure 4 This is a metallographic photograph of the coarse-grained cemented carbide prepared in Example 4.

[0048] Figure 5 This is a metallographic photograph of the coarse-grained cemented carbide prepared in Example 5. DETAILED DESCRIPTION

[0049] The technical scheme of the present invention is further described below by specific embodiments. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0050] (I) Test method

[0051] (1) Density: GB / T 3850-2015 Density determination method for dense sintered metal materials and cemented carbides;

[0052] (2) Rockwell hardness: GB / T 3849.1-2015 Rockwell hardness of cemented carbide (A scale) Part 1: Test method;

[0053] (3) Flexural strength: GB / T 3851-2015 Determination method for transverse fracture strength of cemented carbide;

[0054] (4) Grain size: GB / T 6394-2017 Method for determination of average grain size of metals.

[0055] Example 1

[0056] This embodiment provides a method for preparing a coarse-grained cemented carbide, and the specific steps are as follows:

[0057] S1: 94 kg of coarse-grained tungsten carbide with a Fischer-Tropsch particle size of 7.2 μm, 12 kg of cobalt powder with a Fischer-Tropsch particle size of 1.2 μm, 600 g of tantalum carbide with a Fischer-Tropsch particle size of 1.8 μm and 4.8 kg of PEG 4000 are added to a wet grinder, and 213 kg of grinding rods and 32 L of 92% alcohol by volume are added at a solid-liquid ratio of 0.16 L / kg. The mixture is wet-milled at a speed of 36 rpm for 15 hours and then discharged to obtain a first mixed slurry;

[0058] S2: 94 kg of ultra-coarse tungsten carbide with a Fischer-Tropsch particle size of 25 μm and the first mixed slurry are added into the wet grinder, and 301 kg of grinding rods are added at the same time, and the wet grinding is carried out at a speed of 36 rpm for 18 hours before unloading;

[0059] S3: drying the ball-milled raw material at 90°C for 2h, granulating, and pressing to form a green body;

[0060] S4: sintering the green body at 1520° C., charging Ar gas during high temperature sintering, with an Ar gas partial pressure of 6 MPa, and holding time of 2 h;

[0061] The coarse-grained cemented carbide obtained in Example 1 was subjected to metallographic examination according to GB / T 3488.2-2018. The metallographic photographs are shown in FIG. Figure 1As shown in Figure 2, the average grain size of cemented carbide is 5.0 μm.

[0062] Example 2

[0063] This embodiment provides a coarse-grained cemented carbide and a preparation method thereof, the specific details of which are as follows:

[0064] S1: 144 kg of coarse-grained tungsten carbide with a Fischer-Tropsch particle size of 7.5 μm, 10 kg of cobalt powder with a Fischer-Tropsch particle size of 1.0 μm, 30 g of tantalum carbide with a Fischer-Tropsch particle size of 1.4 μm and 5 kg of 52# paraffin wax are added to a wet grinder, and 232 kg of grinding rods and 35 L of 90% alcohol by volume are added at a solid-liquid ratio of 0.14 L / kg. The materials are wet-milled at a speed of 36 rpm for 28 hours and then discharged to obtain a first mixed slurry;

[0065] S2: Add 96 kg of ultra-coarse tungsten carbide with a Fischer-Tropsch particle size of 20 μm and the first mixed slurry into a wet grinder, and add 276 kg of grinding rods at the same time, wet grind at a speed of 36 rpm for 18 hours and then discharge;

[0066] S3: drying the ball-milled raw material at 100°C for 2h, granulating, and pressing to form a green body;

[0067] S4: sintering the green body at 1480° C., charging Ar gas during high temperature sintering, with an Ar gas partial pressure of 6 MPa, and holding time of 2 h;

[0068] The coarse-grained cemented carbide obtained in Example 2 was subjected to metallographic examination according to GB / T 3488.2-2018. The metallographic photographs are shown in FIG. Figure 2 As shown in Figure 2, the average grain size of cemented carbide is 4.4 μm.

[0069] Example 3

[0070] This embodiment provides a coarse-grained cemented carbide and a preparation method thereof, the specific details of which are as follows:

[0071] S1: 110 kg of coarse-grained tungsten carbide with a Fischer-Tropsch particle size of 8.6 μm, 24 kg of cobalt powder with a Fischer-Tropsch particle size of 1.8 μm, 1500 g of niobium carbide with a Fischer-Tropsch particle size of 2.3 μm and 8.4 kg of PEG 4000 are added to a wet grinder, and 217 kg of grinding rods and 39 L of 94% alcohol by volume are added at a solid-liquid ratio of 0.13 L / kg. The mixture is wet-milled at a speed of 36 rpm for 10 hours and then discharged to obtain a first mixed slurry;

[0072] S2: 165 kg of ultra-coarse tungsten carbide with a Fischer-Tropsch particle size of 20 μm and the first mixed slurry are added into the wet grinder, and 360 kg of grinding rods are added at the same time, and the wet grinding is carried out at a speed of 36 rpm for 14 hours before unloading;

[0073] S3: drying the ball-milled raw material at 110° C. for 3 h, granulating, and pressing to form a green body;

[0074] S4: sintering the green body at 1550° C., filling with Ar gas during high temperature sintering, with an Ar gas partial pressure of 9 MPa, and holding time of 3 h;

[0075] The coarse-grained cemented carbide obtained in Example 3 was subjected to metallographic examination according to GB / T 3488.2-2018. The metallographic photographs are as follows: Figure 3 As shown in Figure 2, the average grain size of cemented carbide is 5.8 μm.

[0076] Example 4

[0077] This embodiment provides a coarse-grained cemented carbide and a preparation method thereof, the specific details of which are as follows:

[0078] S1: 261 kg of coarse-grained tungsten carbide with a Fischer-Tropsch particle size of 6.2 μm, 25 kg of cobalt powder with a Fischer-Tropsch particle size of 0.6 μm, 600 g of tantalum carbide with a Fischer-Tropsch particle size of 0.8 μm, 400 g of niobium carbide with a Fischer-Tropsch particle size of 1.2 μm and 14 kg of PEG 4000 are added to a wet grinder, and 1004 kg of grinding rods and 175 L of 95% alcohol by volume are added at a solid-liquid ratio of 0.35 L / kg. The mixture is wet-milled at a speed of 36 rpm for 12 hours and then discharged to obtain a first mixed slurry;

[0079] S2: 214 kg of ultra-coarse tungsten carbide with a Fischer-Tropsch particle size of 23 μm and the first mixed slurry are added to the wet grinder, and 1002 kg of grinding rods are added at the same time, and the wet grinding is carried out at a speed of 36 rpm for 35 hours before unloading;

[0080] S3: drying the ball-milled raw material at 120° C. for 4 h, granulating, and pressing to form a green body;

[0081] S4: sintering the green body at 1420° C., filling with Ar gas during high temperature sintering, with an Ar gas partial pressure of 4 MPa, and holding time of 1 hour;

[0082] The coarse-grained cemented carbide obtained in Example 4 was subjected to metallographic examination according to GB / T 3488.2-2018. The metallographic photographs are shown in FIG. Figure 4 As shown in Figure 2, the average grain size of cemented carbide is 2.5 μm.

[0083] Example 5

[0084] This embodiment provides a coarse-grained cemented carbide and a preparation method thereof, the specific details of which are as follows:

[0085] S1: 244 kg of coarse-grained tungsten carbide with a Fischer-Tropsch particle size of 7.4 μm, 57 kg of cobalt powder with a Fischer-Tropsch particle size of 1.4 μm, 600 g of tantalum carbide with a Fischer-Tropsch particle size of 0.8 μm and 13.2 kg of PEG 4000 are added to a wet grinder, and 904 kg of grinding rods and 175 L of 95% alcohol by volume are added at a solid-liquid ratio of 0.29 L / kg. The mixture is wet-milled at a speed of 36 rpm for 10 hours and then discharged to obtain a first mixed slurry;

[0086] S2: Add 298 kg of ultra-coarse tungsten carbide with a Fischer-Tropsch particle size of 24 μm and the first mixed slurry into a wet grinder, and add 1080 kg of grinding rods at the same time, and wet grind at a speed of 36 rpm for 24 hours before unloading;

[0087] S3: drying the ball-milled raw material at 110° C. for 5 h, granulating, and pressing to form a green body;

[0088] S4: sintering the green body at 1450° C., charging Ar gas during high temperature sintering, with an Ar gas partial pressure of 7 MPa, and holding time of 2.5 h;

[0089] The coarse-grained cemented carbide obtained in Example 5 was subjected to metallographic examination according to GB / T 3488.2-2018. The metallographic photographs are shown in FIG. Figure 5 As shown in Figure 2, the average grain size of cemented carbide is 3.7 μm.

[0090] Example 6

[0091] The difference from Example 1 is that tantalum carbide is replaced by 600 g of niobium carbide with a Fisher grain size of 1.8 μm.

[0092] Comparative Example 1

[0093] Preparation of coarse-grained cemented carbide.

[0094] The preparation method is the same as that of Example 1, except that 60 kg of coarse-grained tungsten carbide is added in step S1, and 128 kg of ultra-coarse-grained tungsten carbide is added in step S2.

[0095] Comparative Example 2

[0096] Preparation of coarse-grained cemented carbide.

[0097] The preparation method is the same as that of Example 1, except that the coarse-grained tungsten carbide added in step S1 has a Fischer-Matz particle size of 4 μm, and the ultra-coarse-grained tungsten carbide added in step S2 has a Fischer-Matz particle size of 30 μm.

[0098] Comparative Example 3

[0099] Preparation of coarse-grained cemented carbide.

[0100] The preparation method is the same as that of Example 1, except that no tantalum carbide is added in step S1.

[0101] Comparative Example 4

[0102] The difference from Example 6 is that niobium carbide is replaced by 600 g of niobium powder with a Fisher particle size of 1.8 μm.

[0103] Test Example 1

[0104] The performance parameters of the cemented carbides of Examples 1-6 were tested, and the test results are shown in Table 1.

[0105] Table 1 Performance test results

[0106]

[0107] It can be seen from Table 1 that the coarse-grained cemented carbide prepared in Examples 1-6 has excellent comprehensive properties, and at the same time has good strength and fracture toughness, so it can improve the wear resistance of the alloy, greatly increase the service life of the coarse-grained cemented carbide under harsh working conditions, and can be used in road milling, pile foundation rotary drilling, coal mining, tunnel excavation and other fields.

[0108] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values ​​from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values ​​between the listed minimum and maximum values ​​are considered to have been disclosed.

[0109] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A coarse-grained cemented carbide, characterized in that: The raw materials for its preparation include tungsten carbide, a binder, an additive and a molding agent; the additive is tantalum carbide and / or niobium carbide, and based on the total weight of tungsten carbide, the binder and the additive, the amount of tungsten carbide is 89.5wt% to 95.99wt%, the amount of the additive is 0.01wt% to 0.5wt%, and the balance is the binder; The tungsten carbide comprises ultra-coarse-grained tungsten carbide and coarse-grained tungsten carbide. Based on the total weight of tungsten carbide, the content of the ultra-coarse-grained tungsten carbide is 40wt% to 60wt%, and the remainder is coarse-grained tungsten carbide; the Fisher grain size of the ultra-coarse-grained tungsten carbide is 18μm to 25μm, and the Fisher grain size of the coarse-grained tungsten carbide is 6μm to 9μm.

2. The coarse-grained cemented carbide according to claim 1, characterized in that: The binder is cobalt powder. Preferably, based on the total weight of tungsten carbide, cobalt powder and additives, the amount of the cobalt powder is 4wt% to 10wt%, and / or the Fisher particle size of the cobalt powder is 0.6μm to 2.0μm.

3. The coarse-grained cemented carbide according to claim 1 or 2, characterized in that: The additive has a Fisher particle size of 0.8 μm to 2.5 μm.

4. The coarse-grained cemented carbide according to any one of claims 1 to 3, characterized in that: The molding agent is polyethylene glycol and / or paraffin. When the molding agent is polyethylene glycol and paraffin, the weight ratio of the two is (1-3):

1. Preferably, based on the total weight of tungsten carbide, cobalt powder and additives, the amount of the molding agent is 2.0wt%-3.0wt%; and / or the molecular weight of the polyethylene glycol is 1500Da-6000Da, preferably 3000Da-5000Da, and more preferably 3500Da-4500Da.

5. The coarse-grained cemented carbide according to any one of claims 1 to 4, characterized in that: The average grain size of the coarse-grained cemented carbide is 2.4 μm to 6.0 μm; and / or the density of the coarse-grained cemented carbide is 14.20 g / cm 3 ~15.30g / cm 3 .

6. A method for preparing a coarse-grained cemented carbide according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: mixing and grinding coarse-grained tungsten carbide, a binder, an additive and a forming agent to obtain a first mixed slurry; S2: mixing and grinding the ultra-coarse-grained tungsten carbide and the first mixed slurry obtained in step S1 to obtain a second mixed slurry; S3: drying, granulating, and pressing the second mixed slurry obtained in step S2 to obtain a green body; S4: Sintering the green body obtained in step S3 to obtain the coarse-grained cemented carbide.

7. The preparation method according to claim 6, characterized in that: In step S1, the mixed grinding includes a first wet grinding. Preferably, the conditions of the first wet grinding include: a ball-to-material ratio of (1.5-3.5):1, a rotation speed of 20-60 rpm, and a ball milling time of 10 h to 30 h; Preferably, wet grinding media is used in the first wet grinding process. Preferably, the wet grinding media comprises alcohol with a volume concentration of 90-95%. Preferably, the amount of alcohol added is such that the solid-liquid ratio is 0.12L / kg to 0.35L / kg based on the total amount of ultra-coarse-grained tungsten carbide, coarse-grained tungsten carbide, binder and additives.

8. The preparation method according to claim 6 or 7, characterized in that: In step S2, the mixed grinding includes a second wet grinding. Preferably, the conditions of the second wet grinding include: a ball-to-material ratio of (1.1-2.0):1, a rotation speed of 20-60 rpm, and a ball milling time of 10 h to 35 h.

9. The preparation method according to any one of claims 6 to 8, characterized in that: In step S3, the drying conditions include: drying temperature of 80°C to 120°C, and drying time of 2h to 4h; And / or, in step S4, the firing conditions include: a firing temperature of 1410° C. to 1550° C. and a firing time of 1 h to 3 h; Preferably, the firing includes pressure sintering, preferably pressure sintering in an inert gas; preferably, the inert gas includes at least one of nitrogen, argon and helium; and / or, the inert gas partial pressure is 1 MPa to 10 MPa; The pressure sintering is preferably performed in argon gas, and more preferably the argon partial pressure is 1 MPa to 10 MPa.

10. Use of the coarse-grained cemented carbide according to any one of claims 1 to 5 or the coarse-grained cemented carbide prepared by the preparation method according to any one of claims 6 to 9 in road milling, pile foundation rotary drilling, coal mining, and tunnel excavation.

Citation Information

Cited By

  • Ball milling process for ultra-coarse hard alloy

    CN120170090A